Rungia pectinata (Linn.) Nees: A Review of Phytochemical Analysis and Pharmacological Activities - Forid, Md. Shaekh; Azuri, Muhammad Saupi bin; Wan Ishak, Wan Maznah; Hossain, Md. Sanower (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Rungia pectinata L. is an herbaceous weed traditionally used for many years for various disease conditions. Nevertheless, these indigenous medical practices are frequently regarded as self-limiting, necessitating a thorough examination of their purported benefits. This review aims to consolidate existing scientific insights and identify domains requiring additional research. The literature was searched using the keyword "Rungia pectinata" OR "Comb Rungia" in well-known scientific databases, including PubMed, Web of Science, and Scopus, and relevant papers were selected for this review. The leaf juice is used as a cooling agent and to treat smallpox in children, reducing pain and swelling. A paste made from the fresh leaves blended with castor oil can heal tinea capitis, a scaly fungoid scalp infection. This plant has a rich tradition of use in treating different disease conditions, such as hepatitis, acute conjunctivitis, children's dyspepsia, dysentery, and lymphoid tuberculosis. Additionally, it exhibits diverse pharmacological activities like antipyretic, anti-inflammatory, diuretic, analgesic, antifungal, and antibacterial effects. This study found that it has secondary metabolites, such as amino acids, glycosides, phenolics, terpenes, phytosterols, tannins, flavonoids, and carbohydrates. Additionally, a total of 38 isolated compounds were identified in essential oils, with the dominant compounds being trans-phytol, hexahydrofarnesyl acetone, and isophytol. However, the phytochemical compositions varied depending on the type of extraction process. R. pectinata presents a promising avenue for medicinal exploration, deeply rooted in traditional practices. This review underscores the need for a more thorough investigation into its diverse therapeutic applications and encourages further research to unlock the plant's full potential.